Bias Gender dalam Keluarga - Setiawati, Setiawati (Universitas Negeri Padang, 2018)
Research on gender bias in the family (A Study in Padang Complex Singgalang) aims to reveal whether there is gender bias in the family in Padang Singgalang complex, especially in terms of implementation of the family in domestic chores, economic factors or family income and family decision making. This research is a family Sabjek dikompleks Singgalang (mothers and fathers) of which withdrawals are